Nuclear Relations: Retention, Shift, and Quality in Supply Chain Perspectives - Bayu Budiharjo; M. R. Nababan; Riyadi Santosa; Tri Wiratno (International Journal of Supply Chain Management, 2020)
Abstract- This study aims to propose an improved trading environment for purchasing low material and alternatives to reform supply chain management among firms which are the parts manufacturers of nuclear industry. One of the means of construing experience is how elements of nuclear relations are constructed within linguistic constructions. Configurations of nuclear relation elements can be different from one language to another because of different grammar rules. As a particular construction is translated, the configurations may be retained or shifted. This study explores retention and shift of nuclear relation configurations as a result of translation and the effect on translation quality in a supply chain for language translation. Clauses and nominal groups in the original novel Percy Jackson portraying the main character’s character and their Indonesian translation are investigated to reveal how the nuclear relation configurations are retained or shifted in the target language. Further, the correspondence of shift and retention and the accuracy and acceptability of the translation is investigated. The results reveal that nuclear relation configuration does not have direct impact on the accuracy of the translation. The configuration tends to be closer to the acceptability of the translation. Nuclear relation configuration can be retained whenever grammar rules allow in translating from English to Indonesian and be reformulated in situations which require shifts.